2015
DOI: 10.1521/jscp.2015.34.9.731
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety and Cannabis Cravings: The Influences of Parent Injunctive Norms and Tension Reduction Expectancies

Abstract: Objectives-Socially anxious cannabis users are influenced by cannabis expectancies and normative perceptions. The present study examines the influence of psychosocial factors on cannabis use vulnerability factors as the result of interactions between norms perceptions, social anxiety, and expectancies.Methods-Participants were 149 (36.2% female) current cannabis users aged 18-36 (M=21.01, SD=3.09). Hierarchical multiple regressions were employed to investigate the predictive value of the social anxiety X injun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
3
1
2
Order By: Relevance
“…Again, the results here were not significant; the receipt of formal anxiety treatment did not mitigate marijuana use among anxiety‐laden students. This lack of statistical significance appears contrary to prior research suggesting that marijuana is used to cope with anxiety (Buckner et al, ; Foster et al, ; Zvolensky, Schmidt, Bernstein, & Keough, ). Other research has found that one's perceived ability to handle stress may moderate the relationship between marijuana use problems and social anxiety (Buckner, Schmidt, Bobadilla, & Taylor, ), whereas distress tolerance has been shown to be negatively related to coping motives for marijuana use (Semcho et al, ).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Again, the results here were not significant; the receipt of formal anxiety treatment did not mitigate marijuana use among anxiety‐laden students. This lack of statistical significance appears contrary to prior research suggesting that marijuana is used to cope with anxiety (Buckner et al, ; Foster et al, ; Zvolensky, Schmidt, Bernstein, & Keough, ). Other research has found that one's perceived ability to handle stress may moderate the relationship between marijuana use problems and social anxiety (Buckner, Schmidt, Bobadilla, & Taylor, ), whereas distress tolerance has been shown to be negatively related to coping motives for marijuana use (Semcho et al, ).…”
Section: Discussioncontrasting
confidence: 94%
“…As a secondary analysis, the current study was unable to assess for marijuana use problems, which may be uniquely related to anxiety and use of marijuana as a coping mechanism. Additionally, further studies have proposed various other factors that may complicate the pattern between marijuana use and anxiety, including parental attitudes and tension reduction expectancies (Foster, Ecker, Zvolensky, & Buckner, 2015), an individual's temperament in terms of harm avoidance versus novelty seeking (Grunberg, Cordova, Bidwell, & Ito, 2015), distress tolerance (Semcho et al, 2016), and behavioral avoidance (Buckner, Zvolensky, Farris, & Hogan, 2014). Thus, the relationship between marijuana use and anxiety remains quite complex, and these findings certainly add further complexity to our current understanding of this dynamic.…”
Section: Discussionmentioning
confidence: 99%
“…Aquando da recolha de dados, nas conversas tidas com os consumidores foi muito frequente constatar que estes relatavam fumar canábis para reduzir a tensão. Esta constatação reforça a interpretação a favor do argumento de que um dos factores motivadores e desencadeadores do uso da canábis é lidar com e reduzir o efeito negativo das situações com que se confrontam (Foster, Ecker, Zvolensky, & Buckner, 2015).…”
Section: Discussionunclassified
“…Os resultados deste estudo podem contribuir para uma melhor compreensão das variáveis psicológicas associadas ao consumo de canábis e da relação entre elas, contribuindo, assim, para o desenvolvimento de estudos mais aprofundados e específicos, por forma a serem desenvolvidas abordagens e intervenções específicas para esta problemática. Importa não perder de vista que estudos anteriores sugerem que quase um terço dos indivíduos que satisfazem os critérios de diagnóstico para os transtornos de abuso de substâncias também satisfaz os critérios para os transtornos de ansiedade social (Foster et al, 2015).…”
Section: Discussionunclassified
“…Parents convey approval or disapproval of substance use, either consciously or not (Petraitis et al, 1995). Given that parents are important role models, their approval/disapproval has reinforcing value and consequently is a robust predictor of offspring cannabis use, across both early adolescence and into emerging adulthood (Bailey et al, 2016;Foster et al, 2015;Foster et al, 2016;LaBrie et al, 2010a;Napper et al, 2015). Yet, most of this work is done with college samples and is cross-sectional in nature and only one study has explicitly tested this mechanistic pathway.…”
Section: Perceived Parental Approval Of Emerging Adult Cannabis Usementioning
confidence: 99%